1990
DOI: 10.1002/bit.260350104
|View full text |Cite
|
Sign up to set email alerts
|

Integral kinetics of α‐galactosidase purified from Glycine max for simultaneous hydrolysis of stachyose and raffinose

Abstract: alpha-Galactosidase from soybean (Glycine max) was purified by a five-step procedure. The enzyme's natural substrates, raffinose and stachyose, have K(m)'s of 3. 0 mM and 4. 79 mM, respectively. The products, galactose and sucrose, were measured after separation by liquid chromatography. Galactose is a competitive product inhibitor of stachyose and raffinose hydrolysis with a K(i) of 0. 12 mM. We determined these parameters by an integral kinetic approach. Stachyose hydrolysis gives a nearly constant level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…This is very interesting for industrial purposes as the amount of stachyose in soybean products is higher than that of raffinose. Activities on aryl R-D-galactosides as well as on melibiose, raffinose, and stachyose are exhibited by several R-galactosidases, but most of these enzymes present a higher affinity for the trisaccharide raffinose than for the tetrasaccharide stachyose (42). Also, the K m values calculated for the D. hansenii UFV-1 extracellular R-galactosidase (11) with the same substrates (melibiose, raffinose and stachyose) were close to (3); iodoacetamide (4); AgNO 3 (5); NaCl (6); SDS (7); KCl (8); CuSO 4 (9); CaCl 2 (10); -mercaptoethanol (11); raffinose (12); maltose (13); sucrose (14); melibiose (15); D-glucose (16); D-galactose (17); D-mannose (18); lactose (19); stachyose (20) on D. hansenii UFV-1 intracellular R-galactosidase, and (1) without effectors.…”
Section: Resultsmentioning
confidence: 99%
“…This is very interesting for industrial purposes as the amount of stachyose in soybean products is higher than that of raffinose. Activities on aryl R-D-galactosides as well as on melibiose, raffinose, and stachyose are exhibited by several R-galactosidases, but most of these enzymes present a higher affinity for the trisaccharide raffinose than for the tetrasaccharide stachyose (42). Also, the K m values calculated for the D. hansenii UFV-1 extracellular R-galactosidase (11) with the same substrates (melibiose, raffinose and stachyose) were close to (3); iodoacetamide (4); AgNO 3 (5); NaCl (6); SDS (7); KCl (8); CuSO 4 (9); CaCl 2 (10); -mercaptoethanol (11); raffinose (12); maltose (13); sucrose (14); melibiose (15); D-glucose (16); D-galactose (17); D-mannose (18); lactose (19); stachyose (20) on D. hansenii UFV-1 intracellular R-galactosidase, and (1) without effectors.…”
Section: Resultsmentioning
confidence: 99%
“…Quemener and Brillouet (1983) reported that the in vitro hydrolysis rate of ciceritol by a--D-galactosidase is much lower than for raffinose, stachyo- se and verbascose. Porter et al (1990) indicated that hydrolysis of stachyose in soybean seeds is a rate-limiting step and soybean a-galactosidase simultaneously hydrolyzes two substrates: stachyose and raffinose. By analogy, it can be expected that hydrolysis of verbascose and trigalactosyl pinitol A in winter vetch seeds can be limited by the rate of hydrolysis of products: stachyose and ciceritol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Os valores de K M ap para a rafinose (Tabela 4) foram próximos daqueles determinados para α-galactosidase purificada de sementes de soja madura (PORTER et al, 1990), mas menores do que aqueles descritos para a rafinose e as enzimas de Aspergillus fumigatus (De REZENDE e FELIX, 1999) Tanto a C1 quanto a C2 não hidrolisaram substratos sintéticos contendo resíduos de açúcar diferentes de galactose ou contendo galactose na posição β (Tabela 6).…”
Section: Resultsunclassified